FACTORS INFLUENCING THE DEVELOPMENT OF ENDOMETRIAL POLYPS - L. Yu. Bagdasaryan; V. V. Ponomarev; L. Yu. Karakhalis; E. I. Steblo; G. A. Penzhoyan (Кубанский научный медицинский вестник, 2018)
Aim. To determine factors on the background of which there is the formation of polyps in patients of reproductive age. Materials and methods. We examined 75 patients of reproductive age with endometrial polyps, analyzed the anamnesis, ultrasound and histology data.Results. The average age was 31,77±3,56, average BMI 27,4±3,2 kg/m2; there were more than half patients with extragenital pathologies (gastrointestinal tract diseases in 57,33%; endocrine diseases in 52,0%; cardiovascular system – 44,0%); heavy menstruations were in 78,66% patients, infertility – 100%.Conclusion. The determination of risk factors of developing endometrial polyps in reproductive age contributes to the choice of tactics of management of these patients.